New surgical approach for sutureless scleral fixation. Issue 3 (May 2020) - Veronese, Chiara; Maiolo, Chiara; Armstrong, Grayson W; Primavera, Laura; Torrazza, Carlo; Della Mora, Livia; Ciardella, Antonio P
Purpose: The aim of this article is to describe a novel surgical technique for sutureless scleral fixation of an intraocular lens using the newly developed FIL SSF Carlevale IOL (Soleko, Italy). Methods: Four eyes of four patients with poor capsular support were recruited to our study, three resulting from intraocular lens subluxation and one case resulting from traumatic cataract. A novel sutureless sclera-fixated intraocular lens was implanted into the posterior chamber of each eye with sclerocorneal plugs fixating the lens to the wall of the eye. Results: Mean age of patients was 52 ± 16 years, ranging from 35 to 70 years. Mean follow-up was 6.50 ± 1.29 months (range: 5–7 months). Mean preoperative best-corrected visual acuity was 0.50 ± 0.33 logMAR (range: 1–0.3 logMAR). Postoperative best-corrected visual acuity improved to 0.08 ± 0.08 logMAR (range: 0.2–0 logMAR). There was no significant change in the mean intraocular pressure and there were no postoperative complications, such as iatrogenic distortion or breakage of the intraocular lens haptic, intraocular lens decentration, endophthalmitis, or retinal detachment. Discussion: To the best of our knowledge, this is the first report of outcomes using the novel sutureless sclera-fixated FIL SSF Carlevale IOL. This new surgical technique offers a simplified and effective approach for sutureless scleral intraocular lens fixation with good refractive outcomes.